21ST-CENTURY SKILLS IN LANGUAGE EDUCATION: THE IMPORTANCE AND IMPLICATIONS - BAKHROMOVA, Iroda (The Lingua Spectrum, 2025)
The conceptual paper examines the imperative to integrate the 21st-century skills framework, encompassing Life and Career, Innovation and Learning (4C), as well as Information Literacy skills, into modern language education. Although the framework is globally recognized, there are still unique challenges in implementing it in specific linguistic and pedagogical contexts, particularly for learners of agglutinative languages, such as Uzbek, acquiring fusional languages like English. By combining recent literature, this paper identifies the distinct barriers to developing ‘4C’ core skills within these settings. It argues that moving beyond traditional memorization-based methods in teaching foreign languages is not only beneficial but also essential. The paper concludes by proposing a multi-level model for integration, offering practical implications for curriculum design, teacher training, and assessment strategies to foster these vital competencies in language learners, that is to say, preparing them for academic and professional success in a globalized world.